2014
DOI: 10.1260/0263-6174.32.6.465
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Vanadium Nitride Synthesized by Chemical Routes

Abstract: Nanocrystalline vanadium nitride (VN) materials are synthesized by two different routes, namely, the urea route and the ammonia route, using various V 2 O 5 precursors obtained by citric acid-based sol-gel method. The VN nanomaterials obtained are characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and BET method. The XRD patterns show the presence of pure cubic phase with line broadening. The lattice parameters were found to be 4.1266 and 4.1136 Å for the urea route and 4.1125 and 4.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 24 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Previous studies suggested several routes for the synthesis of polycrystalline oxynitrides, such as the use of urea as a nitrogen source, 10,25 microwave synthesis, [26][27][28] hydrothermal synthesis, 29 high-temperature plasma routes, 30 mechanochemical synthesis under pressurized atmosphere, 31 the direct reaction of metal vanadium and nitrogen, and the direct ammonolysis of oxide precursors, aerogels, sulfides and metal amides. [32][33][34][35] In the current study, we focus on VON materials prepared by the ammonolysis route, involving the nitridation of vanadium pentoxide (V 2 O 5 ) by its reaction with gaseous ammonia (NH 3 ) at elevated temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested several routes for the synthesis of polycrystalline oxynitrides, such as the use of urea as a nitrogen source, 10,25 microwave synthesis, [26][27][28] hydrothermal synthesis, 29 high-temperature plasma routes, 30 mechanochemical synthesis under pressurized atmosphere, 31 the direct reaction of metal vanadium and nitrogen, and the direct ammonolysis of oxide precursors, aerogels, sulfides and metal amides. [32][33][34][35] In the current study, we focus on VON materials prepared by the ammonolysis route, involving the nitridation of vanadium pentoxide (V 2 O 5 ) by its reaction with gaseous ammonia (NH 3 ) at elevated temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The surface properties of vanadium oxynitride and related materials are of broad interest for many applications, including protective surface coatings, 1,2 supercapacitors, 3 heterogeneous catalysis, 4 and, recently, the nitrogen reduction reaction (NRR). [5][6][7] In these applications, the surface-specific N− −O interactions are often crucial.…”
Section: Introductionmentioning
confidence: 99%
“…[28b, [43][44] For instance, Mishra et al studied the effect of ammonia annealing temperature on the particle size, BET surface area and pore size distribution of the generated nitrides. [45] Similarly, Panda et al investigated the effect of ammonia-assisted nitridation for differently-prepared WO 3 and CoWO 4 precursors on their crystal structure, surface area and pore texture. [46] Further, Saad et al synthesized mesoporous Ni 3 N and Ni 3 FeN via low-temperature thermal ammonia reduction of NiO and Ni 3 FeO x at 370 °C and 400 °C, respectively.…”
Section: Chemical Methodsmentioning
confidence: 99%
“…For instance, Mishra et al . studied the effect of ammonia annealing temperature on the particle size, BET surface area and pore size distribution of the generated nitrides [45] . Similarly, Panda et al .…”
Section: Synthetic Routesmentioning
confidence: 99%